The effect of a seven-week exercise program on golf swing performance and musculoskeletal measures - Olivier, M. H.; Horan, S. H.; Evans, K. A.; Keogh, J. W. L. (International Journal of Sports Science & Coaching, 2016)
As most golf exercise studies have shown improved golf performance as a result of two or three sessions per week, the present study investigated the effects of a supervised exercise session performed once a week for seven weeks on golf swing variables and musculoskeletal screening measures. Professional Golfers Association of Australia International Golf Institute student golfers (n=43) with a mean±standard deviation handicap of 8.6±8.3 participated in the study. Each golfer performed 10 musculoskeletal tests and a standardised 60-shot golf performance test (TrackMan, Vedbaek, Denmark) on separate days before and after the seven-week program. Significant improvements in a number of musculoskeletal tests (i.e. left leg bridging (6.6%), thoracic extension (62.5%), right thoracic rotation (23.3%), and right (20.8%) and left single leg squat (29.1%)) were observed (all p=0.024); however, no significant differences were observed for any golf swing variables. Future research investigating different training protocols may help to determine whether the type or frequency of training has the greatest influence on golf swing performance. ABSTRACT FROM AUTHOR